Mapping Profile of Critical Thinking Skills on Invertebrate Concepts - Adisti Yuliastrin; Dheanda Devionita; Nelly Yesra; Mery Berlian; Rian Vebrianto (Gagasan Pendidikan Indonesia, 2024)
This research aimed to determine the critical thinking skills possessed by junior high school students. The method used in this research is a survey and the subjects are junior high school students. Techniques for collecting data using test instruments. Based on the results of a survey conducted, In the interpretation results, the highest score was 50%. The self regulation component is the component with the lowest score from students at 20%. It can be seen that the students' level of thinking is still considered a low level of thinking, especially in invertebrate material. This survey research will be the main basis for researchers to conduct further research at the same research location.